The Grammatical Status of The Same - Dixon, R. M. W. (Studia Anglica Posnaniensia, 2009)
The same, consisting of two words (or of clinic-plus-word), functions as a single grammatical item. Basically, it belongs to the determiner slot in phrase structure (together with articles, demonstratives and possessors). Like demonstratives, it may function as a substitution anaphor. But the same also shares some properties with adjectives — it can make up a complete copula complement, it may be the first element of a reduced relative clause, it may be followed by a preposition plus NP, and it has limited function as an adverb.